PENGARUH SENI DAN SOSIAL BUDAYA TERHADAP PERSEPSI MASYARAKAT MENGENAI TATO MENGGUNAKAN STRUCTURAL EQUATION MODELING (SEM) - UMBARA, I GEDE GANDEVA; SUCIPTAWATI, NI LUH PUTU; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 7 No 4 (2018)DO - 10.24843/MTK.2018.v07.i04.p226, 2018)
This study purposed to know the effect of art and socio-culture on the public perception of tattoos. The data used in this study is the primary data collected using a questionnaires distributed to 200 people with 100 non-tattooed people and 100 tattooed people. This study used covariance-based Structural Equation Modeling (SEM) with AMOS software, and used three latent variables such as art, socio-culture and tattoo perception. The results of this study show art and socio-culture have a significant effect on tattoo perception.